Impact of rotavirus vaccine in reducing hospitalization rates in pediatric patients: a single center experience in Italy - Silvia Dettori; Ilaria Cortesia; Marcello Mariani; Anna Opisso; Alessio Mesini; Carolina Saffioti; Elio Castagnola (Taylor & Francis Group, 2021)
Rotavirus is a major cause of acute gastroenteritis in children under 5 years of age, with severe illness occurring in 30-40% of cases. In Italian region of Liguria, vaccination with a two-dose human attenuated vaccine was introduced in 2013. We conducted a retrospective study to assess the impact of rotavirus vaccine on hospitalizations for rotavirus-related gastroenteritis (RVGE) at the IRCCS Istituto Giannina Gaslini. Every hospitalization due to laboratory-confirmed RVGE and acute gastroenteritis of unknown origin (AGUO) in patients aged 0-14 years in the period 2008-2019 were anonymously extracted. Vaccine coverage were obtained from the regional vaccination registry. The results were divided in 2008-2012 (before RV vaccine) and 2013-2019 (after) periods. From 2008 to 2012, there was a continuous reduction of AGUO hospitalizations while RVGE increased. Since 2013, a reduction in hospitalization rate was observed for RVGE with a sharp decrease from 17.81 per 10.000 children in 2012 to 0.79 per 10,000 in 2019, parallel with the ascending values of RV vaccination coverage that increased from 36.3% in 2013 to 63.9% in 2019. A significant negative correlation was found between the proportions of vaccinated newborns and RVGE rates (p = .012). Intussusception-related hospitalization did not show substantial modifications. We confirm vaccination as a safe practice that has a significant impact in pediatric hospitalization rates.